2020
DOI: 10.1103/physrevresearch.2.012020
|View full text |Cite
|
Sign up to set email alerts
|

Two critical localization lengths in the Anderson transition on random graphs

Abstract: We present a full description of the nonergodic properties of wavefunctions on random graphs without boundary in the localized and critical regimes of the Anderson transition. We find that they are characterized by two critical localization lengths: the largest one describes localization along rare branches and diverges with a critical exponent ν = 1 at the transition. The second length, which describes localization along typical branches, reaches at the transition a finite universal value (which depends only … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
69
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(80 citation statements)
references
References 94 publications
10
69
1
Order By: Relevance
“…6, but without collapsing, black dashed lines show the evolution of the maximal |q ε (R)| 2 and its energy with the increasing cutoff radius according to Eqs. (24c), (25) and (38). The insets show the same maximal points of |q ε (R)| 2 in linear scale with the power-law black dashed fitting curves coinciding with the ones in the main panels.…”
Section: Power-law Euclidean Modelsupporting
confidence: 58%
“…6, but without collapsing, black dashed lines show the evolution of the maximal |q ε (R)| 2 and its energy with the increasing cutoff radius according to Eqs. (24c), (25) and (38). The insets show the same maximal points of |q ε (R)| 2 in linear scale with the power-law black dashed fitting curves coinciding with the ones in the main panels.…”
Section: Power-law Euclidean Modelsupporting
confidence: 58%
“…Besides, it is very stimulating to think of the small-world effect in the presence of disorder [90]. It has been found to host unusual physics for non-interacting fermions [91,92], and it would be interesting to study the problem for interacting quantum systems, similarly to what has been done on the Cayley tree [93] for bosons in a random potential. Random exchange spin systems also offer a very promising platform, in particular to explore the issue of infinite randomness criticality [94] against the small-world effect [95].…”
Section: Discussionmentioning
confidence: 99%
“…In many-body systems, this can be considered as a proxy for the non-equilibrium dynamics of local operators after quench [28,60,61] and also as a direct measure for entanglement propagation [60,61]. Our finding gives evidence of the existence of sub-diffusive dynamics over an entire range of parameters, even in a part of the phase diagram where most of the works [29,[37][38][39][40][41][42][45][46][47][48][49][50][51][52][53][54][55][56] agree that eigenstates are ergodic according to standard multifractal analysis of wave functions.…”
mentioning
confidence: 89%
“…the fixed branching number, RRG can be considered as a natural choice to approximate MBL systems [28][29][30] and hope to overcome some of the numerical difficulties that have been mentioned earlier. Apart from the fact that RRG gives a new emphasis on the field of Anderson localization, independently also its own physics is extremely rich [35][36][37][38][39][40][41][42][43][44]. For instance, it has been shown that there is a possibility of a non-ergodic extended (NEE) phase composed of critical states and placed between the ergodic and the localized phase [28,[36][37][38][39].…”
mentioning
confidence: 99%